2011
DOI: 10.1143/apex.4.117101
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced CO$_{2}$ Reduction with GaN Electrode in Aqueous System

Abstract: CO2 reduction with water and light illumination is realized using a gallium nitride (GaN) photoelectrode in which excited electrons induce CO2 conversion at the counter electrode. For the counter electrode, a copper (Cu) plate was chosen. The low affinity and wide gap of the nitride semiconductor enable us to create an electron–hole pair which has a sufficient energy for both CO2 reduction and water oxidation, in spite of the fact that a high energy for CO2 reduction is required. Within this system, the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…The authors have found that gallium nitride (GaN), when used as the anode, is able to reduce CO 2 when combined with an appropriate cathode. 16,17 GaN is one of the few materials that can create excited electron-hole pairs with sufficient energy for CO 2 reduction and water oxidation, which can be operated with no extra bias input or need for sacrificial materials. Another feature is that this system consists of a combination of simple inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have found that gallium nitride (GaN), when used as the anode, is able to reduce CO 2 when combined with an appropriate cathode. 16,17 GaN is one of the few materials that can create excited electron-hole pairs with sufficient energy for CO 2 reduction and water oxidation, which can be operated with no extra bias input or need for sacrificial materials. Another feature is that this system consists of a combination of simple inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The overall performance of Ge doped nanowire PEC CO 2 reduction is also comparable to previous reports, wherein expensive sapphire and/or GaN substrates were utilized. 23,24,26 In summary, we have demonstrated the use of Ge doped GaN nanowire electrode for the PEC reduction of CO 2 into various valuable hydrocarbons, including CH 4 and HCOOH. Compared to the previously reported planar semiconductor electrodes, such defect-free nanowires showed enhanced stability and, importantly, scalability, due to the direct integration with low cost, large area Si substrates.…”
mentioning
confidence: 86%
“…Compared to conventional metal-oxide based photoelectrocatalysts, metal-nitride based catalysts (e.g., Ga(In)N) offer several important advantages, including a high level of stability in aqueous media and tunable energy bandgap across nearly the entire solar spectrum. [12][13][14][15][16][17][18][19][20][21][22] Yotsuhashi et al showed the promising potential of GaN for CO 2 reduction, [23][24][25][26] wherein GaN epilayers grown on sapphire or GaN substrate were used as photoanodes. For practical applications, however, it is highly desired that low cost, large area substrates such as Si can be utilized, instead of the expensive sapphire or GaN substrate.…”
mentioning
confidence: 99%
“…In addition, the bandgap energy of GaN-based materials can be varied from about 0.65 to 6.0 eV by alloying them with InN and AlN, thereby making it possible to design various functional photoelectrodes not only for spectral matching of solar light but also for electrochemical reduction of carbon dioxide to carbohydrate [21]. For the photoelectrode application, porous structures have advantages such as large surface area and low photoreflectance.…”
Section: Introductionmentioning
confidence: 99%